Upgrading the Vietnam semi-quantitative soil classification system - Nguyen Thanh, Tuan; Ho Quang, Duc; Le Thai, Bat; Le Anh, Tuan; Nguyen Quyet, Chien; Lai Quang, Trung; Kikuvi Kyenze, Stanslaus; Tran Thuy, Chi (Vietnam Journal of Earth Sciences, 2022)
A quantitative soil classification system (SCS) has been the aim of generations of Vietnam soil scientists. The SCS is a system of harmonizing the traditional Vietnam SCSs and creating a capability for international exchange. Up to now, there are three partially developed Vietnam official SCSs and three Vietnam semi-quantitative ones. This article aims to upgrade the Vietnam semi-quantitative SCS based on Vietnam's traditional pedogenetic (qualitative) and the World Reference Base for Soil Resources in 2014 (quantitative). For this purpose, a study was conducted to compare and analyze the correlation between the published Vietnam semi-quantitative SCSs and the official ones. Six SCSs were compared and analyzed. The results show that the Vietnam semi-quantitative SCS-2006 was selected to continue adapting and updating. Apart from the necessary adjustments, the study added 12 diagnostic horizons, 4 diagnostic properties, 2 diagnostic materials, 2 soil groups, 11 soil types, and 37 soil sub-types in the Vietnam semi-quantitative SCS-2006. Finally, the Vietnam semi-quantitative SCS includes 25 soil groups, 86 soil types, 492 soil sub-types with 30 diagnostic horizons, 7 diagnostic properties, 6 diagnostic materials, 58 qualifiers, and 9 criteria for defining soil varieties. The system keeps the traditional aspects of Vietnam's official SCSs and allows the exchange of international soil information.